Linear Theory of Electromagnetic Ion Beam Instabilities in the Earth’s Forshock: Peter Gary’s Contributions (1981–1991) - Winske, Dan; Wilson, Lynn B. (Frontiers in Astronomy and Space Sciences, 2022)
We discuss Peter Gary’s contributions to the understanding of the origin and properties of ultra-low frequency (ULF) waves in the Earth’s foreshock during the period when the International Sun Earth Explorer spacecraft (ISEE-1 and -2) provided unique data about the plasma and wave environment in this region. Peter’s work concerning the linear theory of electromagnetic ion beam instabilities is contained in five journal articles and then summarized in a review article, all of which are discussed here. Brief summaries of observations and theory prior to ISEE as well as to later work are also included.